2019
DOI: 10.1002/pssa.201900175
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Atomic Hydrogen Diffusion Behavior by Reaction Kinetic Analysis in Projection Range of Hydrocarbon Molecular Ion for CMOS Image Sensors

Abstract: In this study, two types of hydrogen diffusion behavior in the projection range of a hydrocarbon molecular ion after high-temperature heat treatment for the passivation of interface state defects at SiO 2 /Si interface of the CMOS image sensor is presented. The hydrogen peak concentration in the hydrocarbon ion projection range is observed by secondary ion mass spectrometry analysis after silicon epitaxial growth and the subsequent high-temperature heat treatment. Moreover, the hydrogen peak concentration stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Indeed, a previous study has demonstrated that the concentration of hydrogen that out-diffused from the C 3 H 5 -implanted region at 700 °C is sufficient compared with D it at the SiO 2 /Si interface. 24) Therefore, we consider that D it at the SiO 2 /Si interface obtained by C-V measurement was reduced owing to the termination of the Si dangling bonds (·Si≡Si 3 ) at the SiO 2 /silicon interface with hydrogen outdiffused from the C 3 H 5 -implanted region.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, a previous study has demonstrated that the concentration of hydrogen that out-diffused from the C 3 H 5 -implanted region at 700 °C is sufficient compared with D it at the SiO 2 /Si interface. 24) Therefore, we consider that D it at the SiO 2 /Si interface obtained by C-V measurement was reduced owing to the termination of the Si dangling bonds (·Si≡Si 3 ) at the SiO 2 /silicon interface with hydrogen outdiffused from the C 3 H 5 -implanted region.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we have developed an alternative solution to the technical issue encountered in CMOS image sensor fabrication by hydrocarbon molecular ion implantation. [16][17][18][19][20][21][22][23][24] We have demonstrated the fabrication of a novel silicon wafer with three unique characteristics, namely, the high gettering capability for metallic impurities, the oxygen out-diffusion barrier effect and the hydrogen storage effect in the projection range of hydrocarbon molecular ions. We have already reported that our novel silicon wafer leads to a marked improvement of CMOS device key parameters, such as low dark current and white spot defect density when using the CMOS image sensor manufacturing line.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12][13][14][15][16][17] We have developed silicon epitaxial wafers by hydrocarbon molecular ion implantation to solve the above-mentioned important technical issues of CMOS image sensors. [18][19][20][21][22][23][24][25][26] Hydrocarbon-molecular-ion-implanted silicon epitaxial wafers have been demonstrated to have high guttering capability for metal impurities generated during the CMOS image sensor manufacturing process. [18][19][20][21][22][23] In addition, to the high gettering capability for metal impurities, the hydrocarbon-molecular-ion-implanted region has unique characteristics.…”
mentioning
confidence: 99%
“…For example, it acts as an oxygen diffusion barrier and hydrogen storage. [24][25][26] This hydrocarbon-molecular-ion-implanted silicon epitaxial wafer has been reported to markedly improve important parameters in CMOS image sensors such as dark current and white spot defects. 27 In addition, the reduction in interface state density (D it ) by desorption of hydrogen in the hydrocarbon-molecular-ion-implanted region has been demonstrated by capacitive voltage (CV) measurement and electron spin resonance (ESR) method.…”
mentioning
confidence: 99%